Synconn_build: A python based synthetic dataset generator for testing and validating control-oriented neural networks for building dynamics prediction - Gaurav Chaudhary; Hicham Johra; Laurent Georges; Bjørn Austbø (MethodsX, 2023)
Applying model-based predictive control in buildings requires a control-oriented model capable of learning how various control actions influence building dynamics, such as indoor air temperature and energy use. However, there is currently a shortage of empirical or synthetic datasets with the appropriate features, variability, quality and volume to properly benchmark these control-oriented models. Addressing this need, a flexible, open-source, Python-based tool, synconn_build, capable of generating synthetic building operation data using EnergyPlus as the main building energy simulation engine is introduced. The uniqueness of synconn_build lies in its capability to automate multiple aspects of the simulation process, guided by user inputs drawn from a text-based configuration file. It generates various kinds of unique random signals for control inputs, performs co-simulation to create unique occupancy schedules, and acquires weather data. Additionally, it simplifies the typically tedious and complex task of configuring EnergyPlus files with all user inputs. Unlike other synthetic datasets for building operations, synconn_build offers a user-friendly generator that selectively creates data based on user inputs, preventing overwhelming data overproduction. Instead of emulating the operational schedules of real buildings, synconn_build generates test signals with more frequent variation to cover a broader range of operating conditions. • Synconn_build is an open-source tool designed to address the lack of datasets for benchmarking control-oriented building dynamics prediction models. • The tool automates simulations, data acquisition, and EnergyPlus configuration, guided by user inputs. • Synconn_build prevents data overproduction by selectively creating data, offering a user-friendly approach to dataset generation.